Influence of breastfeeding duration on the incidence of dental caries in preschoolers: a cohort study - Heloísa Helena Barroso; Priscila Seixas Mourão; Rafaela Lopes Gomes; Maria Tereza Pereira de Almeida; Thaís Santos Silva; Joana Ramos-Jorge; Maria Letícia Ramos-Jorge; Izabella Barbosa Fernandes (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: investigate the association between breastfeeding duration and the incidence of severe caries in preschoolers. Methods: a cohort study was conducted with 132 pairs of mothers and children in the city of Diamantina, Brazil. Data collection was performed in 2 moments: when the children were between two and three years of age (baseline- 2013/2014) and after three years (T1-2016/2017). In both moments, children were evaluated for dental caries (International Caries Detection and Assessment System - ICDAS) and a questionnaire was administered to the mothers addressing socioeconomic aspects and thee habits of children. The outcome evaluated was the incidence of severe caries (Dentin caries - ICDAS Codes 5 and 6). Data analysis involved descriptive statistics, chi-squared test and Poisson hierarchical regression with robust variance. Results: children who breastfed for more than 24 months (RR = 2.24 CI95%= 1.23-4.08), those whose parents were separated (RR = 1.73 CI95%= 1.11-2.69), and those with estab-lished/severe caries (RR = 2.74 CI95%= 1.37-5.49) at baseline were at greater risk of incidence of severe caries after three years. Conclusion: breastfeeding for more than 24 months is a risk factor for incidence of severe caries. In addition, family structure and established or severe baseline caries were associated.